In vitro anthelmintic effect of aqueous extract of Croton blanchetiana leaf on sheep endoparasites - Yandra Thaís Rocha da Mota; Ana Karolinne de Alencar França; Marcus Vinicius Gomes Dantas; Renata Cristina Borges da Silva Macedo; João Inácio Lopes Batista Lopes Batista; Karoline Mikaelle de Paiva Soares; Michele Dalvina Correia da Silva; Ana Carla Diógenes Suassuna Bezerra (Revista Contexto & Saúde, 2025)
The development of small ruminants has been hampered by infections related to gastrointestinal endoparasites. This problem arose due to the incorrect use of anthelmintics and inadequate management practices, which led to the emergence of parasite resistance. Given this, herbal medicine offers an alternative approach to parasite control. Among the various options, Croton blanchetianus stands out for its bioactive compounds and demonstrates antibacterial, antifungal, ectoparasiticidal and anthelmintic properties. Thus, the objective of this study was to evaluate the in vitro ovicidal activity of the aqueous extract derived from Croton blanchetianus leaves. For this, fecal samples were collected directly from the rectal ampulla of naturally infected animals, without administration of antiparasitics, for a period of 90 days. When the egg count per gram of feces exceeded 2,000 eggs, these eggs were collected for hatchability testing. Simultaneously, phytochemical analyzes were carried out on the leaves and toxicity tests on Artemia salina. The results revealed that the aqueous extract, at concentrations of 5 %, 2.5 %, 1.25 % and 0.625 %, presented hatching inhibition rates of 81.8 %, 70.0 %, 47.8 % and 40.4 %, respectively. Phytochemical analysis confirmed the presence of secondary metabolites in the extract. Furthermore, the toxicity test demonstrated that the C. blanchetianus extract was non-toxic to Artemia salina at all concentrations tested. Consequently, it can be concluded that the aqueous extract had inhibitory effects on egg hatching due to the presence of several secondary metabolites, thus increasing its potential as an anthelmintic treatment against gastrointestinal parasites in sheep.